The Analysis of the LPG Storage Tank Planning Based on the Potential Demand in Belitung Island - Adiga Putra Alindita; Dwi Nurma Heitasari (Indonesian Journal of Energy and Mineral, 2021)
The growing demand for LPG has increased the number of LPG tanker ships/gas carriers entering X Port, resulting in queues that will impede the distribution of LPG to the people of Belitung Island. PT XYZ in-tends to construct an LPG tank in the X Port area to facilitate LPG distribution on Belitung Island. The tank capacity is expected to meet Belitung Island’s LPG demand for the next five years. The authors forecast the potential demand for the next five years using LPG revenue data from January 2019 to February 2021, with forecasting results from March 2021 to February 2026. The Time Series Method was used to forecast by comparing the smallest MAD (Mean Absolute Deviation) values between the Linear Trend Model and the Exponential Trend Model. According to the forecasting calculations conducted using the linear trend mod-el, the potential demand for February 2026 is 973.4098 Tons with a ten-day stock resistance. According to these calculations, the proposed tank is a spherical tank with a capacity of 1000 tons, which means that the LPG tank stock resistance in the last period, namely February 2026, is 11 days, which is in compliance with the Regulation of the Ministry of Energy and Mineral Resources Number 26 of 2009 concerning the Provision and Distribution of Liquefied Petroleum Gas.